(untitled) (Global Journal of Management and Business Research, 2013)
This paper presents a retrospective critique of my own survey research conducted more than three decades ago in Tehran, Iran. The main finding of the research was that the managers of small companies in Iran had failed to implement the principles of western scientific management in their companies. A summary of the research and its results are presented. A social constructionist critique of the research and its approach is made as a cautionary note to those who continue to advance western theories of management and organizations as universal, "culture-free" and objective facts in non-western countries.